Mechanical properties of bi-directional corrugated honeycomb aluminum filled with expanded polypropylene under quasi-static compression. Issue 6 (2nd November 2021) - Xing, Youdong; Yang, Siyi; Lu, Shiqing; Zhang, Pengfei; An, Yukun; Yu, Wenqiang; Zhai, John
Abstract: In this paper, a porous material–bi-directional corrugated honeycomb aluminum (Bi-DCHA) was manufactured, and quasi-static compression experiments were performed in axial (Y/Z-direction) and radial (X-direction) directions. It was concluded that the mechanical properties in the Y/Z directions were better than those in X-direction. Further, to verify the effect of expanded polypropylene (EPP) on the properties of Bi-DCHA, three different density EPP were used to fill them, and the property of Y/Z-direction was performed. As a result, compared with Bi-DCHA unfilled with EPP, the performance of Bi-DCHA filled with EPP improved, and is better than the sum of EPP and Bi-DCHA unfilled with EPP. Observing the stress-strain curves of the four groups of samples, we can find that the initial peak stress (σP ) of the Bi-DCHA filled with EPP is lower than Bi-DCHA; the stress in the plateau zone (σpl ) increases with the increase of the EPP density. Observing the deformation process of the specimen, it was found that after filling the EPP, the deformation process of the specimen changed from global buckling/tilt mode to local compact plastic deformation mode. The energy absorption effect of Bi-DCHA filled with EPP is stronger than that of unfilled specimen.